Community-based Islamic education: Democratizing learning through local wisdom - MR, Moh Irsyad Fahmi; Anam, Ahmad Muzakkil; Agustinova, Danang Ade; Prasastiawati, Diana; Awalin, Fakhur Rohman Nur; Yaacob, Norazlan Hadi (Universitas Negeri Yogyakarta, 2024)
This study examines the role of community-based education in the context of Islam as a means of democratizing education and integrating local wisdom, motivated by the need for a more inclusive and responsive education system. Using a literature study method, this research analyzes primary and secondary sources related to Islamic education, democratization, and local wisdom. The results reveal that community-based education has strong historical and normative roots in Islamic tradition, reflected in various forms of traditional educational institutions such as mosques, kuttabs, and pesantrens. This educational model is proven to encourage active community participation, decentralization of decision-making, and integration of local values into the curriculum. However, its implementation faces challenges in balancing national standards with local autonomy, as well as potential conflicts between universal Islamic values and local cultural practices. This study highlights the complexity of integrating local wisdom into modern Islamic education in the era of globalization, paving the way for further research on optimal mechanisms for adapting this educational model to increasingly diverse Muslim societies.